Multiple Sequence Alignment and Phylogenetic Analysis of Growth Differentiation Factor 9 Gene for Egg Production in Poultry Species - Pretty Rachuene; Kagisho M Molabe; Thobela L Tyasi (Research in Agriculture Livestock and Fisheries, 2025)
Growth differentiation factor 9 gene (GDF9) is an oocyte-secreted factor which controls the functions of the ovarian cells, regulates the development and caliber of the egg. GDF9 DNA and protein sequences from NCBI were used to computationally investigate molecular genetic variation in poultry species. Results showed that percentage similarities of DNA and protein sequences ranged from 78.45 to 92.80% and 83.63 to 94.74%, respectively. The phylogenetic analysis results showed that chicken and turkey were closely related. The high percent similarities and close relatedness of poultry species show that GDF9 can be used as a candidate gene for improving egg production in poultry species. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 63-72